The relationship between government service provision and life satisfaction for South African individuals - Groenewald, Jean-Marc (My University, 2019)
The present study contributes to the subjective well-being literature by looking at how the provisioning of government service affects subjective well-being in South Africa, how this differs by various groups, and whether the relationships have changed over time, specifically between 2009 and 2016. The study aims to provide an updated analysis of how subjective well-being and government service provision are linked within the current political climate for differing groups within the South African context. This paper utilises the South African Social Attitudes Survey (SASAS) data for both the 2009 and 2016. The SASAS survey is a nationally representative survey. The dependent variable (Y), life satisfaction, is derived from the question in the SASAS data set that is phrased as “Taking all things into consideration, how satisfied are you with your life as a whole these days?”. Ordered probit regression modelling is used in the empirical analysis to explore the indicated research outcomes. The results suggest a decline in the effect that access to government services have on individuals’ life satisfaction in South Africa. In 2009, access to electricity and access to a flushed toilet were both positively and significantly related to SWB. However, in 2016, only access to piped drinking water was statistically significant with a positive effect. This effect was particularly large in 2016 for those living in formal areas and for women, suggesting that service delivery affects different groups’ SWB in different ways. The various control variables (unemployment, education, health, etc.) had the expected effects on SWB given evidence in the existing international and South African literature on this topic, providing some confidence in the specification and data reliability.
A dissertation submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfillment of the academic requirements for the degree of Masters in Development Theory and Policy,
Keywords: Government productivity; Community development--South Africa; Municipal services--South Africa